Peningkatan Kecepatan Pedinginan Pada Sistem Pendingin Sepeda Motor Beat 110cc Dengan Kode Kvy - Miftah Maulana; Reza Setiawan; Aa Santosa (Jurnal Ilmiah Wahana Pendidikan, 2022)
Motorcycle is a means of transportation that can not be separated in modern human life. Simple but has many benefits and is very useful as a means of transportation, also having an affordable price is the reason why many people use motorbikes. Motorcycles themselves, especially automatic motorbikes also have problems that must be solved. This problem arises because the engine of the automatic motor itself is inside the motor body so that the heat transfer is hampered by the motor body itself. This deficiency is what encourages researchers to fix the problem. This repair is done by making a hole in the front of the deck for the air to flow as a cooler. The results showed that after repairs were made, it showed a significant difference in heat transfer, so that the engine became cooler and optimal.